Community-Based Participatory Research: Approaches and Implications for Public Policy - Faslah, Redho; Simamora, Rani; Fikri, Alvian Izzul (Journal Ligundi of Community Service, 2024)
Background: Community-Based Participatory Research (CBPR) has gained recognition as an effective approach for involving community members in the research process. This method aims to address community-specific issues by leveraging local knowledge and fostering collaboration between researchers and community stakeholders. Despite its growing popularity, there is a need to better understand how CBPR approaches can influence public policy and lead to more effective and inclusive policy outcomes. Objectives: This study aims to explore the various approaches utilized in CBPR and examine their implications for public policy. The research seeks to identify best practices in CBPR and assess how these practices can inform and improve policy-making processes. By highlighting successful CBPR initiatives, the study aims to provide insights into how community engagement can enhance policy relevance and effectiveness. Methods: The research employs a mixed-methods approach, combining qualitative case studies with quantitative surveys. Case studies were conducted on several CBPR projects across different sectors, including health, education, and environmental sustainability. Surveys were distributed to participants involved in these projects, including community members, researchers, and policymakers. Data were analyzed to identify common themes, challenges, and outcomes associated with CBPR. Results: The findings reveal that CBPR approaches lead to more inclusive and contextually relevant policy outcomes. Key themes identified include the importance of trust-building, continuous community engagement, and the co-creation of knowledge. Challenges such as resource constraints and power dynamics were also highlighted. The study found that policies informed by CBPR were more likely to address community needs and gain community support. Conclusion: CBPR offers valuable approaches for enhancing public policy through active community involvement. By addressing challenges and leveraging best practices, CBPR can lead to more effective and inclusive policy-making. The study underscores the need for continued investment in CBPR to foster collaborative and sustainable policy solutions that truly reflect the needs and priorities of communities.